(untitled) (International Journal of Physiotherapy, 2018)
Background: Feedback systems give support to athletes or patients and have a positive effect on training control. A feedback system, the virtual coach (VC), was developed. Methods: Two different studies in both fields of application (popular sport, rehabilitation) were conducted. The pushup-study was done to investigate the effect of the VC during a 6-week-training. Results: The results show the positive impact on different parameters, such as motion duration which is closer (EG: 3.13 (± 0.28) s, CG: 1.88 (± 0.4) s) to the three seconds motion duration prescribed in the training routine for the EG (using the VC) compared to the CG (without feedback). The second study addressed the second field of application - the rehabilitation. Eight subjects (transfemoral amputees) conducted an 8-week-training with a particular training device added by mobile sensors and the VC (com-bined system). The gait, the maximum power of hip muscles and the weight distribution war registered before and after the intervention. The results are individual as the subjects are. The improvement of the maximum power (range: 18.6 to 26 %) and the gait velocity (range: 0.05 to 12.39 %) are the most remarkable results. Positive changes in other gait parameters as well as in the weight distribution were observed for the individuals. Conclusion: Summarizing both studies, a positive effect of using the feedback system (VC) can be found. Due to the small sample size and the heterogeneity of the amputee group, a generalized statement cannot be given from the second study with the transfemoral amputees.